Efektivitas Perbandingan Budikdamber Sistem Airlift dengan Budikdamber Biasa pada Budidaya Ikan Lele Dumbo (Clarias gariepinus) - Miranda, Salmanya; Almuqaramah, T.M. Haja; Syahputra, Faisal; Thaib, Azwar (Jurnal TILAPIA, 2025)
The fish farming in buckets (Budikdamber) system using airlift technology is an integrated cultivation method in which fish and plants are reared together in a single container (a polyculture of fish and plants). This system utilizes an airlift mechanism to circulate water and nutrients from the bottom of the fish container to the plant growing area. The airlift functions by injecting air into the lower part of a submerged pipe, which lifts water and nutrient-rich fluid to the surface through air pressure. This study aims to determine the more effective method between Budikdamber with airlift and conventional Budikdamber (without airlift) in the cultivation of African catfish (Clarias gariepinus) and water spinach (Ipomoea reptans Poir). A comparative method was employed by evaluating the performance of both systems using two treatments, each with three replications: Treatment A used the airlift Budikdamber system, while Treatment B used the conventional Budikdamber system. The results showed that the growth performance of African catfish (Clarias gariepinus) was significantly better in Treatment A (airlift system) compared to Treatment B (conventional system). However, the growth of water spinach (Ipomoea reptans Poir)—measured by plant height, fresh weight, and leaf number—showed no significant difference between the two treatments. Based on the t-test, there was a statistically significant difference in the growth performance of African catfish in favor of the airlift Budikdamber system (Treatment A).